Trust and socio-economic indicators: model including religion factor - Меркулова, Т. В.; Коваль, Б. С. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
The article is concerned with the following issues: definitions, indicators of trust were reviewed; the working hypotheses of the research were formed; the choice of factors related to the trust indices was made; cluster analysis of the relationship between individual trust indices and economic indicators was carried out; a correlation analysis of the relationship between individual trust indices and socio-cultural indicators was conducted; a neural network for modeling the general index of trust based on a well-founded set of economic and socio-cultural indicators was developed. The hypothesis about the influence of socio-cultural factors on trust and out of which there was distinguished a relation to a specific religion. By means of correlation analysis and neural networks, it was shown that Protestantism and Catholicism are the most significant religions that affect the general index of interpersonal trust. However, atheism has a more significant impact. Following 198 observations, each of which represented the country for a given year in the period from 1995 to 2014, the neural network produced satisfactory results in forecasting the total trust index on the basis of the following factors: GDP per capita, GINI coefficient, atheism (percentage of population, support such an attitude to religion). The neural network recognized 89.9% of the data and 90% of the test set indicating that the network got adjusted and could be used for modeling. The scatter diagram for a 5% error indicates that most of the data is within the required value. But it should be noted, that the model overestimates trust in Ukraine at the end of the analyzed period. This gives grounds for the assumption that in Ukraine there are additional factors that negatively affect interpersonal trust.